Light-driven self-organization of gold clusters by linearly polarized Gaussian beam. (August 2019) - Liaw, Jiunn-Woei; Huang, Mao-Chang; Huang, Cheng-Wei; Ku, Yun-Cheng; Kuo, Mao-Kuen
Highlight s: The optically organized and bound 2D clusters (trimer, tetramer and pentamer) of multiple Au nanoparticles (NPs) induced by a linearly polarized (LP) Gaussian beam is studied theoretically. Via the surface integration of Maxwell's stress tensor, the optical forces and torques upon every Au NPs are analyzed. The numerical results illustrate that 2D stable-equilibrium clusters with wavelength-scale gaps can be produced at an off-focal plane of a LP Gaussian beam, besides 1D linear array patterns. These nanoparticles are driven to transversely spin by the optical torque even though irradiated by a LP light. There is a range of the off-focal plane for inducing these ordered patterns. Abstract: The mechanism of optically organized and bound 2D clusters of multiple Au nanoparticles (NPs) is studied theoretically. Via the surface integration of Maxwell's stress tensor, the optical forces and torques upon every Au NPs are analyzed. The numerical results illustrate that 2D stable-equilibrium clusters (trimer, tetramer and pentamer) with wavelength-scale gaps can be produced at an off-focal plane of a linearly polarized (LP) Gaussian beam, besides 1D linear array patterns. For example, a trimer with an isosceles triangular pattern can be induced. These stably ordered cluster patterns are due to the plasmon-enhanced long-range interaction of light with these coupled Au NPs. Moreover, there is a range of the off-focal plane for inducing these ordered patterns. Our results are in agreement with the previous experiments [Yan et al. Nat. Commun. 2014; 5: 3751]. In addition, we found that these NPs are driven to transversely spin by the corresponding optical torque even though irradiated by a LP light. The study on optomechanics of the light-driven self-assembly of plasmonic colloids can be applied to 2D array patterning, which is worth further exploiting.